2022
DOI: 10.1038/s41443-022-00583-3
|View full text |Cite
|
Sign up to set email alerts
|

Medications mostly associated with priapism events: assessment of the 2015–2020 Food and Drug Administration (FDA) pharmacovigilance database entries

Abstract: A range of drugs have a direct role in triggering ischaemic priapism. We aimed at identifying: a)which medications are associated with most priapism-reports; and, b)within these medications, comparing their potential to elicit priapism through a disproportionality analysis. The FDA Adverse Event Reporting System (FAERS) database was queried to identify those drugs associated the most with priapism reports over the last 5 years. Only those drugs being associated with a minimum of 30 priapism reports were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, this is the first study documenting the misuse and abuse potential of semaglutide in comparison with both remaining GLP-1 analogues (dulaglutide, liraglutide, exenatide, lixisenatide, tirzepatide, and albiglutide) and the phentermine–topiramate combination. The comparison was carried out here with the help of a range of worldwide, valuable [ 34 , 35 ], pharmacovigilance data, namely those derived from the FAERS. AERs related to semaglutide showed steady and progressive increasing levels during the years 2018–2022; conversely, the phentermine–topiramate-related AERs remained roughly stable, and AERs related to the remaining GLP-1 mimetics appeared to have decreased during the same years.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study documenting the misuse and abuse potential of semaglutide in comparison with both remaining GLP-1 analogues (dulaglutide, liraglutide, exenatide, lixisenatide, tirzepatide, and albiglutide) and the phentermine–topiramate combination. The comparison was carried out here with the help of a range of worldwide, valuable [ 34 , 35 ], pharmacovigilance data, namely those derived from the FAERS. AERs related to semaglutide showed steady and progressive increasing levels during the years 2018–2022; conversely, the phentermine–topiramate-related AERs remained roughly stable, and AERs related to the remaining GLP-1 mimetics appeared to have decreased during the same years.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that normally, PDE5is do not tend to induce priapism if prescribed in therapeutic dosages and under medical control. Harmoniously, a recent pharmacovigilance analysis of the FDA Adverse Event Reporting System database (2015–2020) showed a significant signal for tadalafil regarding priapism while indicating none for sildenafil 26 . Further, by sub‐analyzing the characteristics of priapism cases related to PDE5i, they showed that the majority of these cases were associated with excessive dosage ingestion, unusual indications, and/or concomitant medication/recreational drug use and concluded that PDE5i consumption could not cause priapism without the presentation of precipitating factors.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that normally, PDE5is do not tend to induce priapism if prescribed in therapeutic dosages and under medical control. Harmoniously, a recent pharmacovigilance analysis of the FDA Adverse Event Reporting System database (2015-2020) showed a significant signal for tadalafil regarding priapism while indicating none for sildenafil 26. Further, by sub-analyzing the characteristics of priapism…”
mentioning
confidence: 99%
“…This finding is consistent with that of Schifano et al, who found disproportionate reporting for tadalafil among drugs that are associated with priapism. 28 However, most reports for PDE5Is were related to concomitant drugs known to cause priapism, which were taken at the same time and/or at an inappropriate intake or excessive dosage, such as trazodone, various antipsychotics, intracavernosal prostaglandin injections, and alcohol. This is consistent with the suggestion by Rezaee and Gross that drugs with a higher risk of priapism are commonly taken concomitantly with PDE5Is.…”
Section: Discussionmentioning
confidence: 99%